Optimization of Solid Phase Microextraction Conditions for Volatile Components of Foods by Using Response Surface Methodology - Ceyda Dadalı; Yeşim Elmacı Elmacı (Turkish Journal of Agriculture: Food Science and Technology)
High vacuum steam distillation, simultaneous distillation extraction, steam distillation, purge and trap methods are used for sample preparation in volatile component analysis. Since these methods are difficult and costly to implement, these methods have left their place to the solid phase microextraction technique. Extraction conditions such as extraction temperature, extraction time, sample volume and fiber type should be optimized in order to increase the efficiency of extraction in volatile component analysis with solid phase microextraction in foods. In the optimization of extraction conditions in volatile component analysis of foods, studies have been carried out to utilize the response surface method, which reduces the number of experiments and also examines the interaction effect of the independent variables. In this review, it is aimed to give information about current studies using response surface methodology in optimization of volatile compound analysis of foods using solid phase microextraction technique.